Designing a provider-led multimorbidity care model for fragmented insurance-based health systems: A mixed-methods study in Colombia - Omaira Valencia; Oscar Bernal (PLOS One, 2026)
Multimorbidity the coexistence of two or more chronic conditions is a growing challenge for health systems in low- and middle-income countries (LMICs) structured around single-disease paradigms. In Colombia, insurer–provider fragmentation within the General System of Social Security in Health (SGSSS) compounds this challenge, generating discontinuities in care that disproportionately affect people living with multiple chronic conditions. Despite a national epidemiological characterisation, a World Bank-supported management proposal, and a formal pilot implementation, limited published evidence exists of a sustained, provider-level, evidence-grounded model for multimorbidity care in fragmented, insurance-based systems. A sequential exploratory mixed-methods design was employed, comprising three phases: (1) a structured evidence synthesis to identify operational domains and implementation gaps in multimorbidity care models; (2) evidence-informed conceptual model construction; and (3) expert feasibility consultation using elements of the Nominal Group Technique with healthcare professionals and system stakeholders (n = 11). Phases were sequentially integrated, with each informing the development of the next. Evidence synthesis identified five recurring structural domains and four cross-cutting implementation gaps, which together informed the construction of the Integrated Provider-level Adaptive Multimorbidity Model (IPAM). The IPAM comprises five interdependent provider-level components designed to function within fragmented, insurance-based systems. Expert consultation confirmed operational feasibility (mean 4.3/5), clinical relevance (4.7/5), and territorial adaptability (4.6/5) of the proposed model. The IPAM offers a structured, adaptable conceptual framework for strengthening multimorbidity care within provider institutions (IPS) operating in fragmented, insurance-based health systems. Its core design principles minimum-viable risk stratification, provider-level governance, proactive follow-up, and graduated technology integration — are transferable to analogous LMIC contexts. Prospective implementation and cost-effectiveness evaluation represent the essential next phase of validation.